The Dust-to-Gas Ratio, Size Distribution, and Dust Fall-Back Fraction of Comet 67P/Churyumov-Gerasimenko: Inferences From Linking the Optical and Dynamical Properties of the Inner Comae - Marschall, Raphael; Markkanen, Johannes; Gerig, Selina-Barbara; Pinzón-Rodríguez, Olga; Thomas, Nicolas; Wu, Jong-Shinn (Frontiers in Physics, 2020)
In this work, we present results that simultaneously constrain the dust size distribution, dust-to-gas ratio, fraction of dust re-deposition, and total mass production rates for comet 67P/Churyumov-Gerasimenko. We use a 3D Direct Simulation Monte Carlo (DSMC) gas dynamics code to simulate the inner gas coma of the comet for the duration of the Rosetta mission. The gas model is constrained by ROSINA/COPS data. Further, we simulate for different epochs the inner dust coma using a 3D dust dynamics code including gas drag and the nucleus' gravity. Using advanced dust scattering properties these results are used to produce synthetic images that can be compared to the OSIRIS data set. These simulations allow us to constrain the properties of the dust coma and the total gas and dust production rates. We determined a total volatile mass loss of (6.1 ± 1.5) · 10^9 kg during the 2015 apparition. Further, we found that power laws with q=3.7^+0.57_-0.078 are consistent with the data. This results in a total of 5.1^+6.0_-4.9·10^9 kg of dust being ejected from the nucleus surface, of which 4.4^+4.9_-4.2·10^9 kg escape to space and 6.8^+11_-6.8·10^8 kg (or an equivalent of 14^+22_-14 cm over the smooth regions) is re-deposited on the surface. This leads to a dust-to-gas ratio of 0.73^+1.3_-0.70 for the escaping material and 0.84^+1.6_-0.81 for the ejected material. We have further found that the smallest dust size must be strictly smaller than 30μm and nominally even smaller than 12μm.